EFFECTIVENESS OF THE EXISTING HALAL LAWS IN MALAYSIA - Shirin Asa, Rokshana (Jurnal Syariah, 2018)
The disposition and consumption of halal food products are fundamental issues to be addressed in most Muslim states, especially where people of different religions live together. Laws are enacted in order to regulate and control halal food products. However, in the modern context, the implementation of halal certification laws has become very complex and challenging because of diversity. In view of this, the present study discusses the current amendments and the effectiveness of the existing halal certification laws in Malaysia. Generally, the discussion will be divided into two parts. The first part will explain the Trade Description Act (TDA) 2011 and orders related thereto, namely Trade Description (Definition of Halal) Order 2011, Trade Description (Certification and Marking of Halal) Order 2011 and the Trade Description (Certification and Marking of Halal Fees) Regulations 2011 between 1972 and 2011. The second part discusses the recent amendments from 2011 henceforth. The discussion also examines the power and functions of the Ministry of Domestic Trade, Cooperative and Consumerism (hereafter termed as MDTCC) and local authorities regarding the enforcement of halal laws and the implementation procedures used by Department of Islamic Development Malaysia (JAKIM) for halal certification. It also studies the limitations of JAKIM in its regulations to effectively control the misuse of halal logo and halal certification.